Development and Application in Aspen Plus of a Process Simulation Model for the Anaerobic Digestion of Vinasses in Uasb Reactors: Hydrodynamics and Biochemical Reactions - Pages-Diaz, J (Elsevier Ltd, 2020)
UASB reactors are accepted as a suitable technology for biogas production from the anaerobic digestion of vinasse. To describe correctly the behavior of this type of reactors the hydrodynamics as well as the biochemical processes inside the reactor should be considered simultaneously. This represents a complex task during experiments or in full-scale operation. Yet, the better understanding and description of UASB reactors operation would be greatly improved thanks to process simulation tools, saving time and money. In this regard, the aim of this study was to develop a novel simulation model in Aspen Plus® for UASB reactors treating vinasses. The model integrated ADM1- Flow pattern - Biofilms characteristics and the sulfate reduction process. Simulation results from laboratory, pilot and industrial scales showed differences lower than ±15% respect to the real data. Based on the sulfate reduction process an increment in biogas production of 14% for a SO42-/COD ratio of 0.05 was obtained. In agreement with experimental data, the model predicted a reduction of 5% in methane yield and the reactor failure for SO42-/COD ratio from 0.07 to 0.1 and higher than 0.1 respectively. Sensitivity analysis based on granule size showed an increment of 16% in biogas generation when the granule diameter was reduced from 4 mm to 1 mm. The hydrodynamic parameters (i.e. Peclet number, dispersion coefficient) evaluated by the model, demonstrated the existence of a non-ideal flow in the reactor. © 2019 Elsevier Ltd.